2010
DOI: 10.1200/jco.2009.26.7252
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Molecular Genetic Profiling of Pediatric High-Grade Gliomas Reveals Key Differences With the Adult Disease

Abstract: A B S T R A C T PurposeTo define copy number alterations and gene expression signatures underlying pediatric high-grade glioma (HGG). Patients and MethodsWe conducted a high-resolution analysis of genomic imbalances in 78 de novo pediatric HGGs, including seven diffuse intrinsic pontine gliomas, and 10 HGGs arising in children who received cranial irradiation for a previous cancer using single nucleotide polymorphism microarray analysis. Gene expression was analyzed with gene expression microarrays for 53 tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
611
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(651 citation statements)
references
References 51 publications
31
611
1
8
Order By: Relevance
“…Les caractéristiques histologiques des GBM sont identiques quel que soit l'âge du patient ou la localisation de la tumeur, mais leurs caractéristiques génétiques diffèrent [1][2][3][4]. Par exemple, chez l'enfant, moins de 10 % des tumeurs ont des mutations/amplifications du récepteur à activité tyrosine kinase de l'EGF (epidermal growth factor) (EGFR), ou des mutations des enzymes isocitrate déshydroxygénase 1 ou 2 (IDH1/2), qui caractérisent respectivement la majorité …”
Section: Caractéristiques Génétiques Des Gbm De L'adulte Et De L'enfantunclassified
“…Les caractéristiques histologiques des GBM sont identiques quel que soit l'âge du patient ou la localisation de la tumeur, mais leurs caractéristiques génétiques diffèrent [1][2][3][4]. Par exemple, chez l'enfant, moins de 10 % des tumeurs ont des mutations/amplifications du récepteur à activité tyrosine kinase de l'EGF (epidermal growth factor) (EGFR), ou des mutations des enzymes isocitrate déshydroxygénase 1 ou 2 (IDH1/2), qui caractérisent respectivement la majorité …”
Section: Caractéristiques Génétiques Des Gbm De L'adulte Et De L'enfantunclassified
“…3,4 Large-scale genomic sequencing has also shown that pediatric gliomas are genomically distinct diseases compared to their histologically similar adult counterparts. 5 Moreover, genomic analyses have shown that even within a single demographic group or histological entity, multiple molecular subtypes of disease exist. 6,7 Our increased understanding of the molecular characteristics underpinning glioma pathogenesis and increased precision in defining disease subsets will hopefully lead to the development of treatments that target the molecular aberrations driving their genesis.…”
Section: Human Gliomas Are Genomically Heterogeneousmentioning
confidence: 99%
“…Ancak pediatrik YDG oluşumu, henüz eriş-kin patogenezi kadar netlik kazanmamıştır. [7,8] Evre IV GBM oluşumunda ise LOH 10q, PTEN mutasyonu, DCC geninin ekpresyonunun kaybolması (%50) ve PDGFR-α geninin amplifikasyonu (%10) sorumlu tutulmaktadır. De novo GBM oluşumunda ise sırasıyla EGFR amplifikasyonu ve normalden fazla ekspresyonu, yine MDM2 geninin amplifikasyonu veya normalden fazla ekspresyonu, p16 gen delesyonu (%30-40), LOH 10p ve 10q genleri ile PTEN mutasyonu ile RB geninde değişiklikler rol almaktadır.…”
Section: Etyolojiunclassified